IMPLEMENTASI STANDAR KINERJA PELAYANAN MINIMAL BIDANG ADMINISTRASI & MANAJEMEN KHUSUSNYA MELALUI INDIKATOR PELATIHAN KARYAWAN - Triana Lidona Aprilani; Muhsin Muhsin (Valid: Jurnal Ilmiah, 2016)
The implementation of quality health services each hospital needs to develop minimum service standards (SPM). The purpose of this study was to determine the factors inhibiting and support that affect the achievement of the SPM field of Administration and Management in particular indicators of employee training. This study uses qualitative data analysis. Results of this study of the inhibiting factors in the achievement indicators SPM field of education and training is a workforce that is less, funding is not according to standards, a policy that does not exist, infrastructure is inadequate, management training that has not gone well, while the supporting factors are in an organization that has been accommodated in Local Regulation and the Regent, resource persons from the hospital, the hospital already BLUDs status and socialization forum has been facilitated. Suggestions for this research is to increase the amount of energy, create special policies on education and training in accordance with SPM, additional facilities and infrastructure, improvement of management training, socialization and coordination improved